Bugis settlers in East Kalimantan’s Kutai National Park: their past and present and some possibilities for their future - Vayda, A.P.; Sahur, A. (1996)
What policies should be adopted regarding enclave populations in national parks and other protected areas and how should the policies be implemented? These questions are important for protected areas throughout the world. Andrew P. Vayda and Ahmad Sahur report here on socio-economic and historical research that they conducted in the rapidly industrialising Indonesian province of East Kalimantan to help deal with such questions. They use their findings to make practical recommendations about relocating Bugis farmers and fishers from East Kalimantan's Kutai National Park and to assess relocation as an alternative to maintaining the status quo with respect to settlements within the Park's lowland rainforest. In addition, their findings are used to challenge some widely held generalisations about the impoverished condition of forest settlers, the preferability of land to only cash to those who might be resettled, and the inter-relations between urban/industrial employment and forest destruction. The report is methodologically interesting as well. It shows how data collection and analysis may be guided by the goal of obtaining causal histories of events (including such events as forest-clearing in particular places at particular times and past changes in work and residence by settlers in the National Park). It shows how data collection and analysis, thus guided, may lead to significant research findings not obtained by investigators using rapid appraisal and standard survey methods and pre-set questionnaires. Also featured in the report are some methodological reflections on the value and limitations of applying general knowledge and cultural information, and on the need for information about particular historical events, in studies like Vayda and Sahur's. In their research in and around Kutai National Park in 1996, Vayda and Sahur were resuming a collaboration begun in East Kalimantan sixteen years earlier. Andrew P. Vayda is Professor of Anthropology and Ecology at Rutgers University in New Brunswick, New Jersey, USA, and was, at the time of the research reported here, a Distinguished Visiting Scholar at CIFOR. Ahmad Sahur lectures in anthropology at Hasanuddin University, Ujung Pandang, South Sulawesi, Indonesia, and serves there also as an assistant dean.